The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/cm.10116
|View full text |Cite
|
Sign up to set email alerts
|

Class III β‐tubulin in human development and cancer

Abstract: The differential cellular expression of class III ␤-tubulin isotype (␤III) is reviewed in the context of human embryological development and neoplasia. As compared to somatic organs and tissues, ␤III is abundant in the central and peripheral nervous systems (CNS and PNS) where it is prominently expressed during fetal and postnatal development. As exemplified in cerebellar and sympathoadrenal neurogenesis, the distribution of ␤III is neuron-associated, exhibiting distinct temporospatial gradients according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
188
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(202 citation statements)
references
References 107 publications
4
188
1
3
Order By: Relevance
“…Mature astrocytic markers, such as GFAP, are also described to be expressed in glioma cells [53][54][55] , although Jan et al [51] showed that the malignant progression to a higher degree of invasiveness is associated with an increase in vimentin expression and a progressive loss of GFAP. Besides the expression of immature and astrocytic cell markers, gliomas also express neuronal proteins such as β-III-tubulin [56,57] and MAP2 [58] , both indicators of a high-grade astrocytoma [58] . Similarly, the expression of progenitor and mature oligodendrocytes markers are found in gliomas/astrocytomas [59,60] , although MBP is minimally expressed in GBM [59] .…”
Section: Discussionmentioning
confidence: 99%
“…Mature astrocytic markers, such as GFAP, are also described to be expressed in glioma cells [53][54][55] , although Jan et al [51] showed that the malignant progression to a higher degree of invasiveness is associated with an increase in vimentin expression and a progressive loss of GFAP. Besides the expression of immature and astrocytic cell markers, gliomas also express neuronal proteins such as β-III-tubulin [56,57] and MAP2 [58] , both indicators of a high-grade astrocytoma [58] . Similarly, the expression of progenitor and mature oligodendrocytes markers are found in gliomas/astrocytomas [59,60] , although MBP is minimally expressed in GBM [59] .…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The cells are fixed in 4% paraformaldehyde (158127, Sigma-Aldrich) in D-PBS (Gibco 14190, Invitrogen) for 30 min, and then permeablized/blocked in fresh permeable-blocking solution composed of 5% normal donkey serum (017-000-001, Jackson ImmunoResearch, West Grove, PA), 0.3% Triton X-100 (T9284, Sigma-Aldrich) in 1X D-PBS for 2 h at room temperature. Then, cells are incubated with mouse anti-bIII-tubulin (1:500) antibody (Chemicon MAB1637, Millipore) for overnight at 4 C, washed three times, and incubated with Cy3-labeled donkey anti-mouse IgG (1:500) (Chemicon AP192C, Millipore) for 2 h in the dark.…”
Section: Eb Formation and Differentiationmentioning
confidence: 99%
“…Tubulin consists of · and ß subunits. In mammals, six ß-tubulin isotypes have been identified and the complex variable patterns of their expression denote cellular and functional specificity and diversity (8).…”
Section: Introductionmentioning
confidence: 99%
“…Class III ß-tubulin (ß III) is a neuron-associated isotype that is considered to be one of the earliest neuron-associated cytoskeletal markers and is thought to play an important functional role in neuronal morphogenesis (8). ß III expression is observed throughout the lifetime from early development in the central and peripheral nervous systems and in some nerve tumors, such as high-grade gliomas (9), oligodendrogliomas (10), medulloblastomas (11), retinoblastomas (12), and pheochromocytomas (13).…”
Section: Introductionmentioning
confidence: 99%